2008
DOI: 10.1258/jtt.2007.070602
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of telemedicine by heart disease patients following hospitalization

Abstract: NYHA class III and IV chronic heart failure has been established as a potential indication for telemedical care and monitoring already. We conducted a prospective study to assess the utilization of telemedical services by cardiac patients in order to identify further indications. A total of 540 patients (mean age 59 years) with various heart diseases participated for at least 30 days in a home-based telemedicine service programme. The two primary outcome measures were the rates of symptom-driven telephone call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…Most previous studies have focused on applied telemedicine services for cardiovascular diseases, such as ECG analysis of ST‐segment elevation myocardial infarction, wherein in‐hospital mortality reduced and the percentage of patients with door‐to‐balloon time lower than 60 min increased (Matsuda et al, ). In addition, results indicated that telemedicine monitoring in patients with repeat percutaneous coronary intervention or cardioversion for atrial fibrillation is more effective in identifying cardiac arrhythmia (Morguet, Kühnelt, Kallel, Rauch, & Schultheiss, ); Furthermore, when telemedicine services are provided, there is a reduction in hospital admission rate, length of stay and mortality in patients with chronic heart failure and higher quality of life scores (Lin et al, ; Wakefield et al, ). Telemedicine combines continuous monitoring and real‐time case manager feedback to more effectively meet patient requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies have focused on applied telemedicine services for cardiovascular diseases, such as ECG analysis of ST‐segment elevation myocardial infarction, wherein in‐hospital mortality reduced and the percentage of patients with door‐to‐balloon time lower than 60 min increased (Matsuda et al, ). In addition, results indicated that telemedicine monitoring in patients with repeat percutaneous coronary intervention or cardioversion for atrial fibrillation is more effective in identifying cardiac arrhythmia (Morguet, Kühnelt, Kallel, Rauch, & Schultheiss, ); Furthermore, when telemedicine services are provided, there is a reduction in hospital admission rate, length of stay and mortality in patients with chronic heart failure and higher quality of life scores (Lin et al, ; Wakefield et al, ). Telemedicine combines continuous monitoring and real‐time case manager feedback to more effectively meet patient requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, results indicated that telemedicine monitoring in patients with repeat percutaneous coronary intervention or cardioversion for atrial fibrillation is more effective in identifying cardiac arrhythmia (Morguet, Kühnelt, Kallel, Rauch, & Schultheiss, 2008); Furthermore, when telemedicine services are provided, there is a reduction in hospital admission rate, length of stay and mortality in patients with chronic heart failure and higher quality of life scores (Lin et al, 2017;Wakefield et al, 2008). Telemedicine combines continuous monitoring and real-time case manager feedback to more effectively meet patient requirements.…”
mentioning
confidence: 99%
“…A classical example demonstrating the impact of telemedicine on diagnosis is the event recording of cardiac arrhythmia. [3][4][5] The documentation is a prerequisite for the subsequent diagnosis and therapy. Event recording also enables the correlation between the arrhythmia and the complaints of the patient and allows evaluating the quantity and quality of clinically relevant arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…Zu ähnlichen Ergebnissen kommen mittlerweile auch mehrere kontrollierte Studien in Brandenburg [35], Berlin [36], Bayern (München [37] und Fürth [38]) sowie Baden-Württemberg (Heidelberg [13] Die "ideale" Form eines Telemonitorings sollte modular den Gegebenheiten der jeweiligen Situation angepasst werden können, so dass eine reibungslose Überwachung (Abstimmung bezüglich der Schnittstellen) sowohl im stationären als auch im ambulanten Bereich gewährleistet wird, die zusätzlich auch individuell dem Bedarf im Sinne der benötigten Überwachungsfunktionen (Herzfrequenz, Blutdruck, ST-Strecken, Sauerstoffsättigung, Gewicht, Atemfrequenz und Temperatur) und der Intensität des Monitorings (Event-Recording, "on-demand" vs. kontinuierlich) angepasst werden kann. Zukünftig sicherlich sinnvoll wird die integrierte telemedizinische (Mit-)Betreuung eines "primär" kardialen Patienten mit seinen relevanten Komorbiditäten, wie z.B.…”
Section: Studienergebnisse Aus Deutschlandunclassified